Evaluation of expression of the Hrap and Pflp genes in transgenic banana plants for resistance against Xanthomonas campestris pv. musacearum - Kunert, Karl J. (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.